2018
DOI: 10.1039/c8ra01038b
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide attenuates Aβ25–35-induced neurotoxicity via the TLR4/NF-κB pathway in HT22 cells

Abstract: Alzheimer's disease (AD), a neurodegenerative disorder, is marked by the accumulation of amyloid-β (Aβ) and neuroinflammation which promote the development of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…34 Another relevant study found that Aβ oligomers induced neurotoxicity in HT-22 cells by activating iNOS, leading to increased nitric oxide (NO) production and cell damage. 35 Consistent with our results, Aβ might directly interact with the cell membrane, leading to the activation of signaling pathways such as the NF-κB cascade, ultimately leading to the cleavage of caspase-3. Activated caspase-3 triggered a series of apoptosis-related events, including DNA fragmentation and nuclear disintegration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…34 Another relevant study found that Aβ oligomers induced neurotoxicity in HT-22 cells by activating iNOS, leading to increased nitric oxide (NO) production and cell damage. 35 Consistent with our results, Aβ might directly interact with the cell membrane, leading to the activation of signaling pathways such as the NF-κB cascade, ultimately leading to the cleavage of caspase-3. Activated caspase-3 triggered a series of apoptosis-related events, including DNA fragmentation and nuclear disintegration.…”
Section: Discussionsupporting
confidence: 92%
“…This interference may occur either through the direct binding of Aβ to membrane receptors or through nonspecific binding that leads to the disruption of the lipid membrane. , Previous studies in neuronal cells, such as human neuroblastoma SH-SY5Y cells, have shown that the formation of fibrillar Aβ on cell membranes induces the activation of caspase-3, which is the effector caspase associated with apoptosis . Another relevant study found that Aβ oligomers induced neurotoxicity in HT-22 cells by activating iNOS, leading to increased nitric oxide (NO) production and cell damage . Consistent with our results, Aβ might directly interact with the cell membrane, leading to the activation of signaling pathways such as the NF-κB cascade, ultimately leading to the cleavage of caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that Aβ may be the critical factor in AD pathogenesis [3]. Multiple pathogenic processes, including oxidative stress, inflammatory responses, and apoptosis, have been revealed to be implicated in Aβ-induced neurotoxicity [46]. So far, it is generally accepted that Aβ can contribute to neurodegeneration and neuronal loss in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Through network pharmacology and LC-MS-MS analyses, we identified the important active compounds of QZZD, such as baicalin, geniposide, lithocholic acid, glycine, hyodeoxycholic acid and cholic acid. Among them, baicalin ( Li et al, 2020 ), geniposide ( Huang et al, 2018 ), and glycine ( Ullah et al, 2020 ) could significantly influence neuroinflammation, which suggested that QZZD might reduce neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%